Risk perception of alcohol and tobacco consumption in university students from the health area - Rodriguez de la Cruz, Pedro Javier (Universidad de Sonora, 2022)
Introduction: Alcohol and tobacco consumption are a worldwide public health problem that affects adolescents and young people. Mexico is in tenth place with a per capita consumption of 7.2 liters of alcohol, and currently, approximately 14.9 million Mexican people are smokers. Objective: Evaluate the relationship between risk perception and alcohol and tobacco consumption in university students of health sciences at a public university in Tabasco, Mexico. Methodology: This is a descriptive correlational study, with a sample of 601 students selected by stratified probability sampling. Selection criteria: to be enrolled in nursing, medicine or dentistry programs; incomplete instruments and those who dropped out of the study were removed. The questionnaire of personal data and prevalence of alcohol and tobacco consumption, the questionnaire of risk perception towards licit drug consumption and the Audit test were applied, guaranteeing anonymity, data confidentiality and the right to refuse to participate. Results: The average consumption was 3.6 alcoholic beverages and 2.5 cigarettes per occasion. There was a statistically significant negative relationship between risk perception and number of cigarettes consumed (p<.05) and alcohol consumption (p<.01). Conclusions: The consumption of alcohol and tobacco is present in university students of health sciences; therefore, nursing interventions on the perception of risks of consumption should be established in order to have an impact on the phenomenon of addictions.